Analisis Prinsip Independensi Hakim Konstitusi di Indonesia - Priandita Koswara; Megawati Megawati (Ahmad Dahlan Legal Perspective, 2023)
The purpose of this paper is: to find out the analysis of the principle of independence of constitutional judges in Indonesia. The type of research used is included in normative juridical research because it is carried out through document studies or through literature materials by collecting primary legal materials and secondary legal materials. The legal material obtained was analyzed using qualitative analysis. Meanwhile, the approach method used by the author in this study itself is a conceptual approach. Based on the results of the study, it can be concluded that the independence of judicial power can be understood as independence or independence, in the sense of complete freedom and no interference with judicial power. Judicial power is an independent or independent institution of state power, so there is no interference from any party in the implementation of its duties and authorities. Efforts to reduce the value of independence and political practice towards the Constitutional Court are clearly demonstrated by the legislature.Â  Actions outside these provisions injure the independence of the judiciary which is the most important bulwark of the rule of law in the sense of Article 1 paragraph (3) and Article 24 paragraph (1) of the 1945 Constitution.